2001
DOI: 10.1081/jdi-100108189
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Neurocognitive Dysfunction in Chronic Hemodialysis Patients

Abstract: We sought to determine the prevalence, recognition, and consequences of mental impairment among chronic hemodialysis patients. We administered the Mini Mental Status Exam (MMSE), a brief validated method for assessing cognitive mental status that is commonly used by clinicians, to 84 patients from our dialysis units. To determine the clinical implications of mental impairment, we obtained Kt/V, albumin, protein catabolic rate, blood pressure, and hematocrit values. We found that 21% of subjects had mild mental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 11 publications
(8 reference statements)
0
20
2
Order By: Relevance
“…Conclusion: In contrast to several older studies, there is no association between lower other more recent study failed to appreciate a link between dialysis adequacy and cognitive function [16][17][18] . Several of these studies have important limitations: the study of Kutlay et al [16] and colleagues used only the Mini-Mental State Examination (MMSE) for cognitive assessment while Pliskin et al [17] only studied 16 welldialyzed individuals. Tamura et al [18] performed the most current evaluation of this question, using baseline data from the Frequent Hemodialysis Network trials.…”
Section: Introductioncontrasting
confidence: 45%
“…Conclusion: In contrast to several older studies, there is no association between lower other more recent study failed to appreciate a link between dialysis adequacy and cognitive function [16][17][18] . Several of these studies have important limitations: the study of Kutlay et al [16] and colleagues used only the Mini-Mental State Examination (MMSE) for cognitive assessment while Pliskin et al [17] only studied 16 welldialyzed individuals. Tamura et al [18] performed the most current evaluation of this question, using baseline data from the Frequent Hemodialysis Network trials.…”
Section: Introductioncontrasting
confidence: 45%
“…* Denotes p < 0.05. higher serum albumin level, protein catabolic rate, and interdialysis weight gain. 32 Similarly, results from this study showed significant inverse correlations between serum concentrations of albumin, creatinine, calcium and cognitive and motor performance among all study subjects. These inverse correlations with CRD-series test scores indicate improving cognitive and motor performance (lower tests scores in seconds) with increase in laboratory values of albumin, creatinine, and calcium.…”
Section: Discussionmentioning
confidence: 61%
“…39,40 The discovery of the neuroprotective effects of erythropoietin in preclinical studies has been followed by studies in healthy volunteers where erythropoietin was reported to modulate cognitive function-independent of its hematopoietic effects-exerting beneficial effects on memory retrieval, emotional processing, mood, and verbal fluency. 41 Kutlay et al 32 found no relationship between mini mental state exam score and years on dialysis, Kt/V value, hematocrit value, or erythropoietin use in HD patients. Similarly, no relationship between any of the timerelated parameters in CRD-series tests and duration on dialysis, Kt/V, hemoglobin, or weekly dose of erythropoietin was found in HD or CAPD group.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported mild and moderate to severe mental impairment as measured by the MMSE. [12,13] These findings highlight the need for clinicians to routinely screen hemodialysis patients for mental impairment and develop interventions to improve cognitive status.…”
Section: Discussionmentioning
confidence: 99%